Implementasi manajamen strategis berbasis nilai-nilai dalam meningkatkan daya saing bank syariah di indoenesia: Analisis SWOT terhadap strategi agresif digital banking - Hardanti, Kandita Deswira (Maliki Interdisciplinary Journal, 2025)
The implementation of strategic management based on Islamic values ​​has a significant impact on the competitiveness of Islamic banks. First, in terms of reputation, consistency in adherence to Islamic principles (istiqamah) increases public trust, a crucial asset in the financial sector (Irawan, 2023). Second, operationally, digital innovation focused on mashlahah expands market access and improves service efficiency (Tiara et al., 2023). Third, through collaboration, synergy with Islamic fintech companies strengthens competitiveness through product differentiation and rapid technological adaptation. According to(Hamadou et al., 2024), Islamic banks that incorporate maqasid sharia into their digital strategies not only achieve financial goals but also offer sustainable spiritual values. In a global context, strategies based on Islamic values ​​offer unique advantages because they align with the principles of sustainability and contemporary business ethics. Therefore, strengthening Islamic principles such as mashlahah, amanah, and justice is the foundation for sustainable competitiveness for Islamic banks in Indonesia in the digital era.